Heterose e herdabilidade de caracteres relacionados ao rendimento de grãos em trigo (Triticum aestivum L.) - Tessmann, Elisane Weber (2013)
Wheat is among the most important cereal crops in the world, being significant in the daily diet of large parts of Europe, Americas and Oceania. Brazil is not self-sufficient in this crop, producing less than half of the national demand. Several genetic and environmental factors affect wheat yield. The interaction among genotype and environment results in differential yield response depending of environmental conditions. Thus, the assessment of recommended cultivars and populations formed by the crosses between them, become important tools in helping selection of superior populations. The aim of this study was to evaluate elite cultivars and segregating populations. The assessment was focused on traits influencing yield in order to indicate promising combinations to wheat breeding programs. The experiment was conducted in the winter of 2012, in the Palma experimental farm (CGF/FAEM/UFPel), located in Capão do Leão RS/ Brazil. Parental lines, hybrids (F1) and segregating populations (F2) were sown in a randomized block design with three replications. The experimental units consisted of two 3 meters long lines with 0.3 meters spacing between plants and between lines, with 15 plants per line. The population F1 was obtained in the winter of 2011 and one generation was advanced in greenhouse in 2011/2012 warm season. The following traits were evaluated: plant height (PH); leaf spot (LS); number of spikes per plant (NSP); spike length (SL); spike weight (SW); kernels per spike (KPS); kernels weight per spike (KWPS); spike harvest index (SHI) and plant yield (PY). The analysis of variance showed significant differences for all traits studied. The multiple comparisons of means showed similar behavior for the characters PH, NSP, KPS, SHI and PY. The SL formed two groups where the best group was formed by cultivars: CD 104, Marfim, Nova Era, Ônix, Safira and Tibagi. The cultivars CD 104, Cristalino, Marfim, Nova Era and Raízes were superior regard to SW. The dendrogram formed divided the cultivars into seven groups: group I formed by Abalone; group II by Tibagi; group III by Ônix and Safira; group IV by CD 120; group V by cultivars CD 104 and Nova Era; group VI by Cristalino and Raízes, and group VII formed by Marfim. All populations tested (parents, hybrids and F2) showed differential performance in the assessed traits. Some populations were superior just in F1 (CD 104 x Raízes), others superiors just in F2 (Cristalino x Safira, Nova Era x Raízes), others superiors in F1 and F2 (CD 104 x Nova Era, Abalone x Nova Era), and others inferiors in F1 and F2 (Abalone x Tibagi). Just three combinations showed some characters with significant heterosis, where the combination between Abalone and Nova Era showed high values to NSP (108%), SW (40.62%), KWPS (47.55%) and PY (207.37%). Heritability was higher among families than within families, within blocks or individual based. The higher heritability was 70% for PH. Heritability for the traits studied suggests that the selection must be made in advanced generations; moreover, the selection will be more efficient if performed among families.